A comprehensive database for integrated analysis of omics data in autoimmune diseases - Martorell-Marugán, Jordi; López-Domínguez, Raúl; García-Moreno, Adrián; Toro-Domínguez, Daniel; Villatoro-García, Juan Antonio; Barturen, Guillermo; Martín-Gómez, Adoración; Troule, Kevin; Gómez-López, Gonzalo; Al-Shahrour, Fátima; González-Rumayor, Víctor; Peña-Chilet, María; et al. (BMC bioinformatics, 2021)
Autoimmune diseases are heterogeneous pathologies with difficult diagnosis and few therapeutic options. In the last decade, several omics studies have provided significant insights into the molecular mechanisms of these diseases. Nevertheless, data from different cohorts and pathologies are stored independently in public repositories and a unified resource is imperative to assist researchers in this field.